The Histopathological Pattern of Ovarian Teratomas at a Tertiary Care Centre (Medical Forum Monthly, 2024)
Objective: 1)To determine the frequency and types of various ovarian teratomas amongst various age groups. and 2) To compare the results with other workers. Study Design: Retrospective study. Place and Duration of Study: The study was conducted at the Department of Pathology, Basic Medical Sciences Institute(BMSI), Jinnah Post graduate medical centre(JPMC), Karachi from 1st January 2001 to 31st December 2005. Materials and Methods: 1128 cases of ovarian biopsies were received for histopathological examination at the Department of Pathology, Basic Medical Science Institute, JPMC,Karachi.Out of 365 cases of ovarian neoplasms teratomas were separated, analyzed and classified according to the WHO classification system 1994 and their relative frequencies were recorded. Results: Teratomas account for 14.52% (53/365) of all ovarian neoplasms. Mature cystic teratomas were the most common i.e 86.80%(46/53).Immature teratomas were 9.43%(05/53) followed by special subtypes 3.77%(02/53) Conclusion: Mature cystic teratomas are the most common germ cell neoplasms of ovary. Immature teratomas are rare above 30 years of age.